THE IMPLEMENTATION OF THE E-PLANNING SYSTEM AT THE REGIONAL DEVELOPMENT PLANNING BOARD (BAPPEDA) OF CENTRAL JAVA PROVINCE: A Study on the Application of Government Science at the Axiological Level - Hadi Prabowo; Yudi Rusfiana; Endang Try Setyasih; Dadang Supriatna; Mu’tamirudin Mu’tamirudin; Ida Yunari Ristiani (Lembaga Riset dan Pengkajian Strategi Pemerintahan IPDN, 2024)
ABSTRACT. The government and all elements of society can now utilize development information and communication technology, which is developing rapidly. The government can manage government and provide services to the community more quickly, effectively, efficiently, transparently, and accountable. One way is through development planning through e-planning, as in Central Java Province. The implementation of e-planning in Provincial and Regency/City Regional Development Planning is expected to provide convenience for all rights, both public information and all stakeholders, to access as a reference for participation and monitoring. The implementation of e-planning has objectives that include (1) increasing coordination and shared understanding between central and regional governments in implementing e-planning applications in regional development planning; (2) providing input and sharing regional experiences in developing and utilizing e-planning applications in preparing regional development plan documents. This research was conducted to determine how the e-planning system is implemented at the Central Java Province Regional Development Planning Agency. They were using qualitative descriptive research methods. Data were collected using interviews, questionnaires, literature studies, and documentation. The results of the research show that the implementation of the e-planning system at the Regional Development Planning Agency has been implemented quite well; however, in the process of implementing the e-planning system in Central Java (GRMS), it does not follow the Decree of the Minister of Home Affairs which requires all regional governments to use the SIMBANGDA application. It aims to synergize one integrated data with the Ministry of Home Affairs. The impact caused is the delay in reports on the realization of work carried out by the Regional Leadership Organization (OPD), especially in BAPPEDA Central Java Province, making it very difficult for the Ministry of Home Affairs to keep up with developments. Keywords: Implementation, System, E-planning